Association of oxidative stress, programmed cell death, GSTM1 gene polymorphisms, smoking and the risk of lung carcinogenesis: A two-step Mendelian randomization study - Wang, Yijun; Yang, Qiongling; Zheng, Lingzhen (Frontiers in Physiology, 2023)
Aim: We aimed to examine the association of oxidative stress, programmed cell death, smoking, and the GSTM1 gene in the risk of lung carcinogenesis. The two-step Mendelian randomization will reveal evidence supporting the association of the exposure and mediators with the resulting outcome. Methods: In step 1, we estimated the impact of smoking exposure on lung carcinogenesis and programmed cell death. Our study involved a total of 500,000 patients of European ancestry, from whom we obtained genotype imputation information. Specifically, we genotyped two arrays: the UK Biobank Axiom (UKBB) which accounted for 95% of marker content, and the UK BiLIEVE Axiom (UKBL). This allowed us to unmask the association between smoking exposure and the incidence of lung carcinogenesis. In step 2, we further examined the effects of smoking on oxidative stress, programmed cell death, and the incidence of lung carcinogenesis. Results: Different outcomes emerged from the two-step Mendelian randomization. The GSTM1 gene variant was found to be critical in the development of lung carcinogenesis, as its deletion or deficiency can induce the condition. A GWAS study on participant information obtained from the UK Biobank revealed that smoking interferes with the GSTM1 gene, causing programmed cell death in the lungs and ultimately leading to lung carcinogenesis. The relative risk of developing lung carcinogenesis associated with oxidative stress was significantly high among current smokers (a hazard ratio of 17.8, 95% confidence interval of 12.2–26.0) and heavy smokers (a hazard ratio of 16.6 and a 95% confidence interval of 13.6–20.3) compared to individuals who never smoked. The GSTM1 gene polymorphism was found to be 0.006 among participants who have never smoked, <0.001 among ever-smokers, and 0.002 and <0.001 among current and former smokers, respectively. We compared the effect of smoking within two particular time frames, 6 years and 55 years, and found that smoking’s impact on the GSTM1 gene was highest among participants who were 55 years old. The genetic risk peaked among individuals aged 50 years and above (PRS of at least 80%). Conclusion: Exposure to smoking is a significant factor in developing lung carcinogenesis, as it is associated with programmed cell death and other mediators involved in the condition. Oxidative stress caused by smoking is also a key mechanism in lung carcinogenesis. The results of the present study highlight the association between oxidative stress, programmed cell death, and the GSTM1 gene in the development of lung carcinogenesis.